Online Course on First Aid in Emergency Medicine on the International Coursera Platform - A. A. Anisimov; E. V. Kiyasova; Y. V. Valeeva; A. T. Garaev; M. S. Kaligin; V. M. Satdarova; A. Y. Anisimov; A. P. Kiyasov (Неотложная медицинская помощь)
The pandemic of the novel coronavirus infection (COVID-19) has had an enormous impact on the education system. Higher educational institutions were forced to adapt to remote interaction with students and urgently switch to online learning. Currently, there are many educational platforms, among which one of the leading is the Californian Coursera service. In 2020, Kazan Federal University developed and published the first Coursera course on first aid — “Staying Alive! First Aid in Emergency”. The purpose of the current study was to demonstrate the course results in one calendar year. We analyzed the general indicators of Coursera — the global online learning platform. We reviewed the course indicators from December 21, 2020, to December 21, 2021. The research assesses the advantages and disadvantages of using online courses in the medical education system. It was concluded that massive open online courses effectively teach theoretical disciplines. In case of implementation of applied courses, it is necessary to search and introduce new approaches for practical skill development.